Revisiting Selaginella diversity in Java (Indonesia) through combined ecological and taxonomic reassessment - AHMAD DWI SETYAWAN; TATIK CHIKMAWATI; MIFTAHUDIN MIFTAHUDIN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO (Society for Indonesian Biodiversity, 2026)
Abstract. Setyawan AD, Chikmawati T, Miftahudin, Sutarno, Sugiyarto, Sunarto. 2026. Revisiting Selaginella diversity in Java (Indonesia) through combined ecological and taxonomic reassessment. Biodiversitas 27 (1): d270150. https://doi.org/10.13057/biodiv/d270150. Selaginella species have traditionally been distinguished mainly by vegetative traits. Because these traits vary with environmental conditions, the taxonomy of this lycophyte genus has remained complex, especially in tropical Asia. In Java, species diversity estimates remain inconsistent among classical floristic treatments, global databases, and recent field observations. This study reassessed Selaginella diversity in Java using field surveys, herbarium examination, taxonomic standardization, and ecological analyses. A total of 1,962 occurrence records were compiled across multiple habitat types and elevational zones. Species identities were verified through comparison of field collections, herbarium specimens, and published taxonomic references. Ecological structuring was analyzed using descriptive habitat analysis, Principal Component Analysis (PCA), and Non-metric Multidimensional Scaling (NMDS). The reassessment recognized 21 confirmed Selaginella species in Java, consisting of 17 native non-endemic taxa, two endemic taxa, and two introduced or naturalized species. Species richness was highest in humid submontane forests, whereas disturbed habitats contained simplified assemblages dominated by ecological generalists. NMDS analysis indicated significant habitat differentiation (ANOSIM: R = 0.684; p = 0.001 after 999 permutations), while several historically recognized taxa, including S. ascendens, S. springiana, and S. caudata, were not retained as independent species because of extensive overlap with broader species complexes. These results suggest that relying solely on vegetative morphology may overestimate Selaginella species richness in Java. This assessment updates our knowledge of Selaginella diversity in Java by integrating field observations, herbarium evidence, and ecological analyses. Conservation efforts should prioritize humid forest habitats, particularly submontane areas, which support the highest diversity and several habitat-specialist Selaginella species.